2019
DOI: 10.1111/jth.14602
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cysteine thiol‐based linkages in ADAMTS13 in support of a non‐proteolytic regulation of von Willebrand factor

Abstract: BackgroundADAMTS13, a plasma metalloprotease, cleaves von Willebrand factor (VWF) to regulate its function. Additionally, ADAMTS13 is thought to regulate lateral association of VWF multimers to form fibrillar structures through its free thiols.ObjectiveThe purpose of the present study is to obtain direct evidence for ADAMTS13 to engage in thiol/disulfide exchange reactions.MethodsCovalent complexes between ADAMTS13 and VWF were determined by agarose gel electrophoresis under nonreducing conditions. Free thiols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Manufacture and characterisation of purified recombinant human ADAMTS13 (rADAMTS13, Takeda, Vienna, Austria) from a Chinese hamster ovary cell line has been described previously [ [26] , [27] , [28] ]. The rADAMTS13 product used in our investigation is the same as the investigational drug candidate identified as TAK-755, SHP655, or BAX 930 in clinical trials for hereditary thrombotic thrombocytopenic purpura ( ClinicalTrials.gov Identifier: NCT02216084 ) and for sickle cell disease ( ClinicalTrials.gov Identifier: NCT03997760 ).…”
Section: Methodsmentioning
confidence: 99%
“…Manufacture and characterisation of purified recombinant human ADAMTS13 (rADAMTS13, Takeda, Vienna, Austria) from a Chinese hamster ovary cell line has been described previously [ [26] , [27] , [28] ]. The rADAMTS13 product used in our investigation is the same as the investigational drug candidate identified as TAK-755, SHP655, or BAX 930 in clinical trials for hereditary thrombotic thrombocytopenic purpura ( ClinicalTrials.gov Identifier: NCT02216084 ) and for sickle cell disease ( ClinicalTrials.gov Identifier: NCT03997760 ).…”
Section: Methodsmentioning
confidence: 99%
“…In loop L9 in CUB1, the unpaired Cys 1275 (that we substituted to Ser) is not present in other CUB domains. Previous studies have reported the ability of Cys 1275 to undergo redox reactions that may regulate VWF function (40)(41)(42). We certainly found that, without the C1275S mutation, there appeared to be some dimerization of the recombinant CUB1-2 domains in S2 cells.…”
Section: Discussionmentioning
confidence: 50%
“…mations: the open, closed, and intermediate either as a monomeric protein 15,36 or a possible oligomeric form in solution or plasma. 37 Lowering pH and binding of ADAMTS-13 to a substrate such as VWF (D4 domain) or an antibody against the various C-terminal domains of ADAMTS-13 may stabilize multiple intermediate conformations of ADAMTS-13 with a different maximal rate of catalysis 15,22,26 or convert ADAMTS-13 from its "closed" and more stable conformation to an "open" but less stable conformation. [14][15][16]18,27 The "open" ADAMTS-13 species are found to be dramatically increased in patients with acute iTTP, then reduced or normalized during clinical remission or essentially undetectable in the healthy individual.…”
Section: Discussionmentioning
confidence: 99%
“…ADAMTS‐13 is known to exhibit in multiple intermediate conformations: the open, closed, and intermediate either as a monomeric protein 15,36 or a possible oligomeric form in solution or plasma 37 . Lowering pH and binding of ADAMTS‐13 to a substrate such as VWF (D4 domain) or an antibody against the various C‐terminal domains of ADAMTS‐13 may stabilize multiple intermediate conformations of ADAMTS‐13 with a different maximal rate of catalysis 15,22,26 or convert ADAMTS‐13 from its “closed” and more stable conformation to an “open” but less stable conformation 14‐16,18,27 .…”
Section: Discussionmentioning
confidence: 99%